Splenectomy for haematological diseases: comparison between laparoscopic and open procedures - Gomaa, Emad; Khalil, Magdy (International Surgery Journal, 2017)
Background: In some hematological diseases, the spleen may become enlarged, inflamed and causes destruction of normal blood elements. Laparoscopic splenectomy (LS) was first prescribed in 1991 by Delaitre et al and since that date, it gained a steadily increasing worldwide agreement as an option for splenectomy in patients with hematological diseases. It was reported that this can be performed safely and effectively, with lower incidence of morbidity and mortality. The objective of the study was to compare laparoscopic with open splenectomy as regard its benefits and hazards in haematological diseases. Methods: This prospective study had been conducted in General Surgery Department, Sohag Faculty of Medicine. The study included patients with haematological diseases indicated for elective splenectomy, during the period from January 2015 to June 2017. Twenty patients were included for open surgery (OS) and 20 cases were included for laparoscopic splenectomy (LS). Results: Surgical time was significantly longer in LS than OS group. There was significant correlation between surgical time and splenic size in both groups. Most of the LS patients had been operated upon using the anterior approach (65%). Hospital stay after operation in the LS group was much less than the OS group. Return of off-bed activities, bowel movements, oral intake and drain removal were longer but not significantly different compared to LS figures. Conclusions: Laparoscopic splenectomy for haematological indications can be done safely for the properly selected patients with less blood loss and hospital stay but it requires more operative time as compared to conventional splenectomy.